Physiotherapy and the Elderly from 2010 to 2026: A Bibliometric Study - Gina Fazrina; Wita Hana Puspita (Rifa'Institute, 2026)
Introduction: The rapid increase in the elderly population has led to a rising prevalence of multimorbidity and has substantially expanded academic literature and evidence-based practice data, particularly in rehabilitation and physiotherapy. Objective: This study aimed to conduct a performance analysis and science mapping of global publications on geriatric physiotherapy, focusing on longitudinal publication trends, geographical contributions, intellectual network visualization, and emerging research trends through bibliometric analysis. Method: Data were retrieved from the Scopus database for the 2010-2026 period using the keyword strategy “physiotherapy AND elderly”. The data were then processed and visualized using VOSviewer to analyze research networks and thematic clusters. Results and Discussion: A total of 8,026 articles were identified and analyzed. Publication volume peaked in 2025 (n = 1,199; 14.94%), with the United States emerging as the leading contributor, producing more than 2,250 articles. A significant thematic shift was observed in keyword trends, moving from “RCT” and “strength” toward “telehealth” and “accessibility”. Conclusion: The transformation of study variables demonstrates that the geriatric physiotherapy research landscape has undergone a paradigmatic evolution, shifting from laboratory-based experimental approaches toward an integrated digital health ecosystem.